Hubungan Sarapan Dengan Prestasi Siswa SD Di Masa Pandemi Covid-19 - Nourmayansa Vidya Anggraini; Serri Hutahaean (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: The COVID-19 pandemic at the end of 2019 resulted in changes in learning conditions with the implementation of school from home (SFH) for children. On the other hand, children are the hope of the nation in the future. School children are the nation's investment, the nation's next generation. It is necessary to prepare the children to become qualified, healthy, moral, and valuable human beings for society. One of the habits that must be a concern is having breakfast at home when SFH conditions. Breakfast habits on a person have a positive impact in carrying out daily activities. Breakfast has benefits in supporting the nutritional status and learning achievement of children. It happened because there is a supply of optimal blood glucose levels for the needs of the learning process. The purpose of this study was to analyze the relationship between breakfast and student achievement.Methods: This research method is to uses a cross-sectional study design. The sample of this study was students in grades 1-5 of private elementary schools in Depok with a sample of 242 students. The sampling technique used is simple random sampling. As many as 73.9% of students always have breakfast in the morning.Results: There is a relationship between breakfast habits and student achievement with a p-value of 0.000Conclusion: A child must take the time to eat breakfast with quality nutrition to concentrate more on learning and improve their learning achievement.